Life cycle costs and asset management for protective structures against natural hazards - Hoffmann, Markus; Donev, Valentin; Brauner, Michael (ce/papers, 2023)
With increasing risks from natural hazards in alpine regions in Austria OEBB‐Infra and Hoffmann‐Consult have developed a consistent methodology for condition assessment, prediction, and life cycle optimization of protective structures. Based on a thorough assessment of the asset stock standardized life cycles for key structures like rockfall and avalanche protection structures have been derived. The developed life cycle models allow a generalized assessment of asset condition, residual service life, and remaining asset value. In contrast to typical transport assets, protective structures are both subject to natural aging processes and random events with a certain occurrence rate. Beyond standardized life cycles on network level an adjustment to project level is necessary to account for actual condition development and asset specific events. The paper provides an overview on the developed generic life cycle with application to rockfall protection structures with prices 2022 in Austria.